2017
DOI: 10.1017/s0950268817002527
|View full text |Cite
|
Sign up to set email alerts
|

Rubella vaccination in India: identifying broad consequences of vaccine introduction and key knowledge gaps

Abstract: SUMMARYRubella virus infection typically presents as a mild illness in children; however, infection during pregnancy may cause the birth of an infant with congenital rubella syndrome (CRS). As of February 2017, India began introducing rubella-containing vaccine (RCV) into the public-sector childhood vaccination programme. Low-level RCV coverage among children over several years can result in an increase in CRS incidence by increasing the average age of infection without sufficiently reducing rubella incidence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…Studies have also noted that the MMR immunization status among children was well below 50%. The Indian government, therefore, had included the Rubella vaccine in the National Immunization Program from 2017 [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also noted that the MMR immunization status among children was well below 50%. The Indian government, therefore, had included the Rubella vaccine in the National Immunization Program from 2017 [6].…”
Section: Discussionmentioning
confidence: 99%
“…The measles, mumps, and rubella (MMR) vaccine was available in India since 2000, but only recently, i.e., in 2017, the Rubella-containing vaccine was introduced in the National Immunization Schedule [6]. It, therefore, is imperative that the current Rubella vaccination is insufficient, and the virus may still be circulating among the population, which poses a threat to pregnant women and the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis: Following respiratory transmission of rubella infection, replication of the infection is thought to happen in the nasopharynx and territorial lymph hubs 53 . A viremia happens 5 to 7 days after the introduction with spread of the infection all through body 54 . Transplacental contamination of the embryo happens amid viremia.…”
Section: Stagementioning
confidence: 99%
“…This has implications for the age targeting of vaccines or other intervention measures. In another mathematical modelling study, Winter et al (2018) showed that incorporating age-mixing patterns decreased the projected estimates of reductions in congenital rubella syndrome attained from introducing public-sector rubella vaccination (Winter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%